Daily evolution of urban heat islands in a Brazilian tropical continental climate during dry and rainy periods - Amorim, Margarete Cristiane de Costa Trindade [UNESP] (Elsevier, 2020)
High temperatures are typically recorded in tropical continental climate regions, with heat intensified by urban heat islands. This research attempts to investigate the intensity and maintenance of heat islands in the lower atmosphere and their spatial distribution during different periods of the day using multicriteria modeling. The present study was conducted in Presidente Prudente city, located west of São Paulo State, Brazil, between south latitudes 22°18′ and 22°06′ and west longitudes 51°47′ and 51°34′; its 2019 population is estimated at 228,743 inhabitants (IBGE, 2019). Air temperature and humidity data were recorded by a meteorological network comprising 26 points distributed throughout the intraurban and surrounding country. Data collection took place during both the dry and rainy seasons' most representative months (August and December 2015, respectively), in evenly spaced periods of the day (0 h, 3 h, 6 h, 9 h, 12 h, 15 h, 18 h, and 21 h). For the integration of primary and secondary data, descriptive statistics of simple and multiple linear regression were adopted. Results show that the heat islands' magnitude and continuity in different periods of the day vary according to surface characteristics (land use, relief, and vegetation) and the city's climatic seasonality. The highest and lowest magnitudes were recorded during the dry rainy season, respectively. It is believed that urban heat islands analysis will enable the subsidizing of territorial management and urban planning, and it will lead to a healthier development of cities, which will enhance societal sustainability.
Keywords: Local scale; Multicriteria analysis; Presidente Prudente - Brazil; Spatial modeling; Urban heat island (UHI)